Crossing Total Occlusions Using a Hydraulic Pressure Wave: Development of the Wave Catheter - Sakes, Aimee; Lageweg, Menno; van Starkenburg, Remi I. B.; Sontakke, Saurabh; Spronck, Jo W. (Frontiers in Medical Technology, 2022)
With the ongoing miniaturization of surgical instruments, the ability to apply large forces on tissues for resection becomes challenging and the risk of buckling becomes more real. In an effort to allow for high force application in slender instruments, in this study, we have investigated using a hydraulic pressure wave (COMSOL model) and developed an innovative 5F cardiac catheter (L = 1,000 mm) that allows for applying high forces up to 9.0 ± 0.2 N on target tissues without buckling. The catheter uses high-speed pressure waves to transfer high-force impulses through a slender flexible shaft consisted of a flat wire coil, a double braid, and a nylon outer coating. The handle allows for single-handed operation of the catheter with easy adjusting of the input impulse characteristic, including frequency (1–10 Hz), time and number of strokes using a solenoid actuator, and easy connection of an off-the-shelf inflator for catheter filling. In a proof-of-principle experiment, we illustrated that the Wave catheter was able to penetrate a phantom model of a coronary Chronic Total Occlusion (CTO) manufactured out of hydroxyapatite and gelatin. It was found that the time until puncture decreased from 80 ± 5.4 s to 7.8 ± 0.4 s, for a stroke frequency of 1–10 Hz, respectively. The number of strikes until puncture was approximately constant at 80 ± 5.4, 76.7 ± 2.6, and 77.7 ± 3.9 for the different stroke frequencies. With the development of the Wave catheter, first steps have been made toward high force application through slender shafts.